Exact soliton solutions of some Nonlinear Dispersive Equations - Patanjali Sharma; Saurabh Kapoor (International Journal of Mathematics And its Applications, 2025)
The functional variable method provides an efficient means of deriving exact soliton solutions for nonlinear partial differential equations. In this study we applied the functional variable method to find soliton solutions of nonlinear dispersive equations. The obtained results are novel and have significant applications in contemporary research areas of mathematical physics.